2019
DOI: 10.1080/2162402x.2019.1652540
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages induce CD47 upregulation via IL-6 and correlate with poor survival in hepatocellular carcinoma patients

Abstract: CD47 is known to be involved in phagocyte-mediated tumor clearance; however, its expression, clinical significance, and regulatory mechanism in hepatocellular carcinoma (HCC) remain poorly understood. In the present study, we found that upregulation of CD47 expression on tumor cells was correlated with poor overall survival and recurrence-free survival in patients with HCC. Abundance of macrophages (Mφs) infiltration was found in CD47 + tumor tissues. Mechanistic studies revealed that IL-6 derived from tumorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 50 publications
3
53
0
Order By: Relevance
“…In this study, we also identified that the elevated CD47 expression is correlated with poor survival in HCCs, which is consistent with previous observations [25,[47][48][49][50][51]. In 2015, William C Chapman et al have shown that blocking CD47 with specific antibodies has therapeutic efficacy in human HCC [52].…”
Section: Agingsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we also identified that the elevated CD47 expression is correlated with poor survival in HCCs, which is consistent with previous observations [25,[47][48][49][50][51]. In 2015, William C Chapman et al have shown that blocking CD47 with specific antibodies has therapeutic efficacy in human HCC [52].…”
Section: Agingsupporting
confidence: 91%
“…To elucidate the clinical significance of the upregulated immune checkpoints, we analyzed the relationship between these genes and overall survival (OS) of HCC patients. The results show that only two genes are significantly associated with poor OS: CD276 (B7-H3) (P = 0.014, Figure 2A) and CD47 (P = 0.039, Figure 2B), consistent with previous reports [20][21][22][23][24][25]. All the others do not have a statistically significant relationship with survival ( Supplementary Figure 1).…”
Section: The Expression Patterns and Clinical Significance Of Immunomsupporting
confidence: 89%
“…30 Interleukin (IL)-6 has been demonstrated to upregulate CD47 expression on hepatoma cells by activating the signal transducer and activator of transcription 3 (STAT3) pathway. 31 In addition, LMP1 upregulated c-myc via IL-6 induction followed by Jak3/STAT3 activation 32 and it also upregulated PD-L1 via the STAT3, activator protein (AP)-1, and nuclear factor (NF)kappa B pathways. 19 Therefore, we infer that LMP1 may upregulate CD47 expression via the c-myc/IL-6/STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the overabundance of CD47 may potentially play an important role in tumor cell evasion. [22][23][24][25][26][27] Soluble CALR can be passively released or actively secreted from cells, as this occurs in the context of massive cell death upon anticancer chemotherapy. Moreover, CALR can be secreted by macrophages stimulated by toll-like receptor (TLR) agonists and then contributes to the recognition and phagocytosis of adjacent tumor cells.…”
Section: Immunosuppression; Calreticulin Secretion; Immune Checkpointmentioning
confidence: 99%